Familia y cultura de los joyeros cataquenses - Sara Lafosse, Mercedes Giesecke (2006)
The present article is part of a thesis of and undergraduate licentiate degree in anthropology: Jewel production and reproduction of culture in Catacaos, defended in 1990. It affirms to the importance of the bond between the traditional forms of social organization and their importance for the productive organization of the artisan jewelry shop, and the patriarchal norm on which is based the authority of the factory and its corresponding social relations. Thus it can be said that it conserves the traditional values of the family that generates the productive confidence in the spouses and the transmission of the technical-productive and commercial knowledge to the spouses, the children and other close friends. Thus they assure work for all. Modernity is represented by the young generations, they but no longer retain this same model of traditional production.